Advances in the preclinical characterization of the antimicrobial peptide AS-48 - Cebrián, Rubén; Martínez-García, Marta; Fernández, Matilde; García, Federico; Martínez-Bueno, Manuel; Valdivia, Eva; Kuipers, Oscar P.; Montalbán-López, Manuel; Maqueda, Mercedes (Frontiers in Microbiology, 2023)
Antimicrobial resistance is a natural and inevitable phenomenon that constitutes a severe threat to global public health and economy. Innovative products, active against new targets and with no cross- or co-resistance with existing antibiotic classes, novel mechanisms of action, or multiple therapeutic targets are urgently required. For these reasons, antimicrobial peptides such as bacteriocins constitute a promising class of new antimicrobial drugs under investigation for clinical development. Here, we review the potential therapeutic use of AS-48, a head-to-tail cyclized cationic bacteriocin produced by Enterococcus faecalis. In the last few years, its potential against a wide range of human pathogens, including relevant bacterial pathogens and trypanosomatids, has been reported using in vitro tests and the mechanism of action has been investigated. AS-48 can create pores in the membrane of bacterial cells without the mediation of any specific receptor. However, this mechanism of action is different when sensitive parasites are studied and involves intracellular targets. Due to these novel mechanisms of action, AS-48 remains active against the antibiotic resistant strains tested. Remarkably, the effect of AS-48 against eukaryotic cell lines and in several animal models show little effect at the doses needed to inhibit sensitive species. The characteristics of this molecule such as low toxicity, microbicide activity, blood stability and activity, high stability at a wide range of temperatures or pH, resistance to proteases, and the receptor-independent effect make AS-48 unique to fight a broad range of microbial infections, including bacteria and some important parasites.